Next of kin - Schulze, Klaus 1947-2022 (Severin Films, 2019)
"Linda Stevens has just inherited Montclare, a retirement home left to her by her late mother. When she finds her mother's diary she reads tales of mysterious events within the house - taps turning themselves on and off, candles lighting and voices in the night. When history begins to repeat itself Linda's nightmares are just the beginning. Montclare hides a dark secret and she is soon fighting for her life." [amazon.de]
Original: Australien, Neuseeland 1982
Special features: commentary with director Tony Williams and producer Tim White ; commentary with Mark Hartley & cast members Jackie Kerin, John Jarrett & Robert Ratti ; House of psychotic women intro By Kier-La Janisse for Morbido TV ; extended interviews from Not Quite Hollywood ; Return to Monteclare: Location revisit, 2018 ; deleted scenes ; Before the night is out: Ballroom footage, 1979 ; trailers ; alternate German opening ; image gallery ; Tony Williams short films
Keywords: Film; Blu-Ray-Disc